Ultimate Strength Prying Models for Bolted T-stub Connections - Swanson, James A. (Engineering Journal, 2002)
Several recognized prying models are discussed and evaluated using experimental data collected during 21 component tests conducted as part of a SAC investigation at the Georgia Institute of Technology as a basis. Four existing prying models are considered in addition to the model that appears in the European design specification. A modification of an existing design model is proposed.